Associations between biopsychosocial factors and transportation patterns of older adults residing in Klang Valley, Malaysia - Mohd Rosnu, Nurul Syuhada; Ishak, Wan Syafira; Abd Rahman, Mohd Harimi; Shahar, Suzana; Musselwhite, Charles; Mat Ludin, Arimi Fitri; Hamid, Tengku Aizan; Abdul Latiff, Abdul Rais; Singh, Devinder Kaur Ajit (Frontiers in Public Health, 2023)
Aging is associated with physiological changes in multiple systems in the body and may impact the transportation choices of older adults. In this study, we examine the associations between biopsychosocial factors and the transportation choices of Malaysian older adults. One hundred and nineteen (119) older adults, aged 60 and above, living in Klang Valley, Malaysia were recruited for this cross-sectional study. Participants were interviewed face-to-face to obtain sociodemographic data, health status (whether there were and, if yes, the number of comorbidities), outdoor mobility and transportation patterns, Instrumental Activity Daily Living (IADL) status and cognitive function. Participants’ physical performance (dominant handgrip strength, 10-meter walk, and timed up and go tests), hearing threshold (pure tone audiometry), and vision function (visual acuity, contrast sensitivity) were measured. Transportation patterns of older adults were categorised into three groups, that is, flexible (using public transport and/or private vehicles), using only private vehicles and restricted (relying on others or walking). The majority (51%) of participants were in the ‘using only private vehicles’ group, followed by the ‘flexibles’ (25%) and the ‘restricted’ (24%). Factors significantly associated with the restricted transportation group were: a) being female (AdjOR 15.39, 95% CI 0.86 to 23.39, p <0.001); b) being Malay (AdjOR 21.72, 95% CI 0.36 to 16.12, p < 0.001); c) having higher number of comorbidities (AdjOR 14.01, 95% CI 0.20 to 13.21, p = 0.007); and d) being dependent in IADL (AdjOR 13.48, 95% CI 0.51 to 1.78, p = 0.002). Further information is needed to enable such older adults as older women, those with comorbidities and poorer functional status to access transportation, especially to meet their health care needs.